a/(x+y) - b/(x-y) = 1

b/(x+y) + a/(x-y) = (a^2-b^2)/(2ab)

Let u = (x+y) and v = (x-y) and c = (a^2+b^2)/(2ab)

(1) a/u - b/v = 1

(2) b/u +a/v = c so multiply (1) by a and (2) by b

(3) a^2/u - ab/v = a

(4) b^2/u +ab/v = bc Add together to get

(a^2+b^2)/u = bc+a or

u = (a^2 + b^2)/(bc + a)

Substituting into (1) we get

a/((a^2+b^2)/(bc+a)) - b/v = 1

a(bc+a)/(a^2+b^2) - 1 = b/v

(abc +a^2 - a^2 + b^2)/(a^2+b^2) = b/v

(abc + b^2)/(a^2+b^2) = b/v

v = (a^2+b^2)/(ac + b)

u+v = 2x and u-v=2y so

2x = (a^2 + b^2)/(bc + a) + (a^2+b^2)/(ac+b)

x = 1/2(a^2+b^2)(1/(bc+a)+1/(ac+b))

x = 1/2(a^2+b^2)(((ac+b)+(bc+a))/((ac+b)(bc+a)))

x = 1/2(a^2+b^2)(4ab(a+b)(c+1))/(4ab(ac+b)(bc+a))

x = (a^2+b^2)(a+b)(2abc + 2ab)/((2abc+2b^2)(2abc+2a^2))

Now 2abc = a^2+b^2 so

x = (a^2+b^2)(a+b)(a^2 + 2ab + b^2)/((a^2 + 3b^2)(3a^2 + b^2))

x = (a^2+b^2)(a+b)^3/((a^2+3b^2)(3a^2+b^2))

2y = (a^2 + b^2)/(bc + a) - (a^2 + b^2)/(ac+b)

y = 1/2 (a^2+b^2)(1/(bc+a) - 1/(ac+b))

y = 1/2(a^2+b^2)(((ac+b)-(bc+a))/((ac+b)(bc+a)))

y = 1/2(a^2+b^2)(4ab(a-b)(c-1))/(4ab(ac+b)(bc+a))

y = (a^2+b^2)(a-b)(2abc - 2ab)/((2abc+2b^2)(2abc+2a^2))

Now 2abc = a^2+b^2 so

y = (a^2+b^2)(a-b)(a^2 - 2ab + b^2)/((a^2 + 3b^2)(3a^2 + b^2))

y = (a^2+b^2)(a-b)^3/((a^2+3b^2)(3a^2+b^2))

So the answer is

x = (a^2+b^2)(a+b)^3/((a^2+3b^2)(3a^2+b^2))

y = (a^2+b^2)(a-b)^3/((a^2+3b^2)(3a^2+b^2))

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now